Volunteering, happiness and public policy - Martin Binder; Andreas Freytag (Max Planck Institute of Economics, 2012)
Is the activity of volunteering something that benefits the volunteer as well as the recipient of the volunteer's activities? We analyze this relationship and apply matching estimators to the large- scale British Household Panel Survey (BHPS) data set to estimate the causal impact of volunteering on happiness. We take into account personality traits that could jointly determine volunteering behaviour and happiness. We find that the causal impact of volunteering on happiness is positive and increasing over time if volunteering is sustained. In a quantile analysis, we find that this effect seems to be driven by reducing the unhappiness of the less happy quantiles of the well-being distribution. We test the robustness of our findings and discuss their relevance for public policy.
Keywords: 330; volunteering; happiness; altruism; generosity; public policy; BHPS; Ehrenamtliche Arbeit; Altruismus; Zufriedenheit; Persönlichkeitspsychologie; Großbritannien